FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DIARE PADA BALITA DI WILAYAH PESISIR - Windi Ayu Anggraini; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Coastal communities are people who live in areas adjacent to the sea where the maoritas work as fishermen. Coastal communities are people who are vulnerable to disease due to their environmental conditions, especially at a young age such as toddlers. Diarrhea is a problem that often occurs, especially in children under five, many factors affect the occurrence of diarrheal diseases in toddlers, especially in coastal areas. The purpose of this study is a literature study that summarizes what factors affect the occurrence of diarrhea in toddlers in coastal areas. The method used by this research is a literature study which looks for several articles related to this research. 6 categories of articles that fall into the criteria with several problem factors that occur. Many factors influence the incidence of diarrhea in toddlers in coastal areas